2006
DOI: 10.1002/gepi.20171
|View full text |Cite
|
Sign up to set email alerts
|

Familial aggregation of ischemic stroke in young women: the Stroke Prevention in Young Women Study

Abstract: We conclude that young-onset stroke aggregates in families and that the magnitude of aggregation increases with decreasing proband age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
46
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 15 publications
2
46
1
Order By: Relevance
“…For TIA, ischemic stroke, and subclinical lesions in the brain, the association with MA has been demonstrated in case-control and crosssectional studies, summarized in meta-analyses, [25][26][27] and demonstrated in large longitudinal studies. 3,4,28 Due to the association between migraine (mostly MA) and ischemic stroke, it is of interest whether migraine is similarly associated with coronary heart disease as well. Although some studies yielded negative results, 29 case reports 30 and cohort studies 9 found an association between migraine and chest pain, and with ischemic electrocardiographic changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For TIA, ischemic stroke, and subclinical lesions in the brain, the association with MA has been demonstrated in case-control and crosssectional studies, summarized in meta-analyses, [25][26][27] and demonstrated in large longitudinal studies. 3,4,28 Due to the association between migraine (mostly MA) and ischemic stroke, it is of interest whether migraine is similarly associated with coronary heart disease as well. Although some studies yielded negative results, 29 case reports 30 and cohort studies 9 found an association between migraine and chest pain, and with ischemic electrocardiographic changes.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] MA seems also to be associated with ischemic heart disease, claudication, and cardiovascular mortality. [7][8][9] Indeed, it has been speculated that migraine may be a risk factor for atherosclerotic disease in general.…”
mentioning
confidence: 99%
“…Controversial topics included whether migraine without aura (MO) was also a risk factor to stroke, if the association also happened in men, and whether migraine was associated with other forms of cardiovascular disease 3 . The field has advanced considerably in recent years, with the publication of evidence that MA is indeed an established risk factor for subclinical ischemic lesions of the brain 4 , as well as for ischemic stroke, particularly among women of younger age 5,6 . The association has also been shown in men 7 .…”
mentioning
confidence: 99%
“…The relationship was stronger in young women, and was magnified by the use of hormonal contraception or by tabagism 1 . Controversial topics included whether migraine without aura (MO) was also a risk factor to stroke, if the association also happened in men, and whether migraine was associated with other forms of cardiovascular disease 3 .The field has advanced considerably in recent years, with the publication of evidence that MA is indeed an established risk factor for subclinical ischemic lesions of the brain 4 , as well as for ischemic stroke, particularly among women of younger age 5,6 . The association has also been shown in men 7 .…”
mentioning
confidence: 99%
“…The field has advanced considerably in recent years, with the publication of evidence that MA is indeed an established risk factor for subclinical ischemic lesions of the brain 4 , as well as for ischemic stroke, particularly among women of younger age 5,6 . The association has also been shown in men 7 .…”
mentioning
confidence: 99%